The Metastable XBP1u transmembrane domain defines determinants for intramembrane proteolysis by signal peptide peptidase - Lipp, Sara Suna; Lorenzoni, Alessandra; Lemberg, Marius (Cell reports, 2019)
Summary - Unspliced XBP1 mRNA encodes XBP1u, the transcriptionally inert variant of the unfolded protein response (UPR) transcription factor XBP1s. XBP1u targets its mRNA-ribosome-nascent-chain-complex to the endoplasmic reticulum (ER) to facilitate UPR activation and prevents overactivation. Yet, its membrane association is controversial. Here, we use cell-free translocation and cellular assays to define a moderately hydrophobic stretch in XBP1u that is sufficient to mediate insertion into the ER membrane. Mutagenesis of this transmembrane (TM) region reveals residues that facilitate XBP1u turnover by an ER-associated degradation route that is dependent on signal peptide peptidase (SPP). Furthermore, the impact of these mutations on TM helix dynamics was assessed by residue-specific amide exchange kinetics, evaluated by a semi-automated algorithm. Based on our results, we suggest that SPP-catalyzed intramembrane proteolysis of TM helices is not only determined by their conformational flexibility, but also by side-chain interactions near the scissile peptide bond with the enzyme’s active site.
Gesehen am 24.04.2019